Fetal Subcutaneous Fat Thickness as a Predictor of Macrosomia - M. A. Lebedeva; Ch. G. Gagaev (Вестник рентгенологии и радиологии, 2019)
Objective: to estimate fetal subcutaneous fat (SCF) thickness, by using ultrasound findings. To analyze the relationship between the antenatal SCF thickness measurements at different sites and the presence of fetal macrosomia.Material and methods. Fetometry was done in 53 pregnant women: a study group included 34 (64%) pregnant women with different types of diabetes mellitus and a control group consisted of 19 (36%) pregnant women without this condition. In addition to standard biometric parameters, SCF thickness was measured at three sites (mid-third of the shoulder, thigh, and anterior abdominal wall) in all fetuses. Eleven and three babies were born with macrosomia in the study and control groups, respectively.Results. The weight of newborns in the study group was significantly higher than that in the control group (3,928±543 and 3,458±610 g, respectively; p=0.0056).The greatest diagnostic value in predicting a large fetus at birth was shown by SCF thickness measurements in the thigh area in the control group and in the shoulder area in the study group. The SCF thickness was 3 mm and more in the mid-third of the thigh and 2.5 mm and more in the mid-third of the shoulder, which are predictors of a large fetus.Conclusions. Fetometric measurements of the estimated fetal weight are extremely important in obstetric practice, as this conclusion may affect delivery timing and mode. The basic formulas are not always accurate, especially in cases of fetal macrosomia. The SCF thickness is an additional marker for macrosomia and can be used even in cases of difficult visualization.